Case Report: TAFRO syndrome misdiagnosed as liver cirrhosis due to persistent abdominal distension - Ma, Luyuan; Gu, Ruolan; Ma, Luzhuo; Li, Xiaoting; Yang, Lan; Xie, Peng; Xiao, Xuelan; Gao, Feng; Liu, Fang; Shen, Chuan; Zhao, Caiyan (Frontiers in Immunology, 2025)
This report described a male patient presenting with recurrent fever, fatigue, persistent abdominal distension, and diarrhea, who was repeatedly misdiagnosed with decompensated cirrhosis at multiple hospitals. The diagnostic process was complex, ultimately leading to the diagnosis of TAFRO syndrome through lymph node and bone marrow biopsies, following 18F-FDG PET/CT imaging. The patient initially responded to treatment, while later succumbed to severe intra-abdominal infection and multiple organ failure. TAFRO syndrome, a rare subtype of Castleman disease, is frequently misdiagnosed due to limited clinical awareness, delaying appropriate treatment. This case highlighted the diagnostic challenges and therapeutic considerations associated with TAFRO syndrome, providing insights for clinical practice based on the existing research.